Fluorescent Chitosan-Europium hydroxyapatite beads for drug delivery - Joana Bahamonde-Duarte; Sarah Briceño; Karla Vizuete; Alexis Debut; Luis J. Borrero-González; Gema González (Carbon Trends)
Fluorescent Chitosan-Europium-doped hydroxyapatite beads (HAp:xEu3+/CS with 0 ≤ x ≤ 0.2) were synthesized for the delivery of ciprofloxacin as a model drug. Europium-doped hydroxyapatite nanoparticles were synthesized using the hydrothermal method and thermally treated at 600 ∘C for 2 h. Hydroxyapatite nanoparticles were combined with chitosan to form the beads. The beads were characterized using Fourier transform infrared spectroscopy, fluorescence microscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, luminescence spectroscopy, and ultraviolet–visible spectroscopy. Chitosan-Europium-doped hydroxyapatite beads reduce the initial burst release of ciprofloxacin and extend the release period, making the beads suitable for sustained potential drug delivery applications. The results reveal that the fluorescence and emission properties were enhanced by the interaction of ciprofloxacin with the beads. These beads offer a combination of optical properties and prolonged ciprofloxacin release with several advantages over conventional immediate-release formulations that could improve therapeutic efficacy.